Fate and cometabolic degradation of benzo[a]pyrene by white-rot fungus armillaria sp. F022 - Hadibarata, Tony (2012)
Armillaria sp. F022, a white-rot fungus isolated from a tropical rain forest in Samarinda, Indonesia, was used to biodegrade benzo[a]pyrene (BaP). Transformation of BaP, a 5-ring polycyclic aromatic hydrocarbon (PAH), by Armillaria sp. F022, which uses BaP as a source of carbon and energy, was investigated. However, biodegradation of BaP has been limited because of its bioavailability and toxicity. Five cosubstrates were selected as cometabolic carbon and energy sources. The results showed that Armillaria sp. F022 used BaP with and without cosubstrates. A 2.5-fold increase in degradation efficiency was achieved after addition of glucose. Meanwhile, the use of glucose as a cosubstrate could significantly stimulate laccase production compared with other cosubstrates and not using any cosubstrate. The metabolic pathway was elucidated by identifying metabolites, conducting biotransformation studies, and monitoring enzyme activities in cell-free extracts. The degradation mechanism was determined through the identification of several metabolites: benzo[a]pyrene-1,6-quinone, 1-hydroxy-2-benzoic acid, and benzoic acid.